Specialist foragers in forest bee communities are small, social or emerge early. Issue 8 (24th May 2019) - Smith, Colleen; Weinman, Lucia; Gibbs, Jason; Winfree, Rachael
Abstract: Individual pollinators that specialize on one plant species within a foraging bout transfer more conspecific and less heterospecific pollen, positively affecting plant reproduction. However, we know much less about pollinator specialization at the scale of a foraging bout compared to specialization by pollinator species. In this study, we measured the diversity of pollen carried by individual bees foraging in forest plant communities in the mid‐Atlantic United States. We found that individuals frequently carried low‐diversity pollen loads, suggesting that specialization at the scale of the foraging bout is common. Individuals of solitary bee species carried higher diversity pollen loads than did individuals of social bee species; the latter have been better studied with respect to foraging bout specialization, but account for a small minority of the world's bee species. Bee body size was positively correlated with pollen load diversity, and individuals of polylectic (but not oligolectic) species carried increasingly diverse pollen loads as the season progressed, likely reflecting an increase in the diversity of flowers in bloom. Furthermore, the seasonal increase in pollen load diversity was stronger for bees visiting trees and shrubs than for bees visiting herbaceous plants. Overall, our results showed that both plant and pollinator species' traits as well as community‐level patterns of flowering phenology are likely to be important determinants of individual‐level interactions in plant–pollinator communities. Abstract : Bees that specialize during a foraging bout are better pollinators, yet little is known about this behaviour across species. The authors examine pollen loads from 55 bee species, and find that bees often specialize during a foraging bout, but that species' traits affect an individual's propensity for this behaviour.